For a Transdisciplinary Approach to Genetic Translation Studies: Archives of the English Renaissance - Cordingley, Anthony (TTR, 2023)
This article explores translation manuscripts from the early modern period, including those of Sir Thomas Wyatt, Sir Henry Savile, Queen Elizabeth I, and newly discovered materials of the King James Bible translators. It analyses the treatment of these manuscripts by specialists of the period, finding a source of inspiration for archival research in translation studies. Focusing on the English Renaissance, four main sites are identified as likely sources of translation drafts for future research. The benefits of a transdisciplinary dialogue between early modern literary history, biblical studies, and genetic translation studies are foregrounded—the orthodoxy that genetic criticism should be confined to authorship from the 18th century onwards is therefore categorically refuted.